Neodymium and hafnium boundary contributions to seawater along the West Antarctic continental margin - Rickli, Jörg; Gutjahr, Marcus; Vance, Derek; Fischer-Gödde, Mario; Hillenbrand, Claus-Dieter; Kuhn, Gerhard (Earth and Planetary Science Letters, 2014)
ISSN:0012-821X ISSN:1385-013X